2022
DOI: 10.18006/2022.10(5).1100.1108
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors of Infectious Bovine Rhinotracheitis in Dairy Cattle of Chitwan, Nawalpur and Rupandehi Districts of Nepal

Abstract: The cross-sectional study from July 2018 to September 2018 was conducted to determine the seroprevalence and risk factors of Infectious Bovine Rhinotracheitis (IBR) in cattle of the Chitwan, Nawalpur, and Rupandehi districts of Nepal. The existence of antibodies against IBR was investigated in 92 serum samples obtained systematically from 55 cattle herds using Indirect-ELISA. A questionnaire interview was done to collect individual and herd-level data. The association between categorical variables and the outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…Disease was found to affect exotic and crossbred cattle in India during inception than native breeds. In Slovenia and Colombia HF cow breed (Hostnik et al, 2021) and in Nepal's Jersey breed of cattle have shown higher prevalence than other breeds (Sanjay et al, 2022). One frequent risk factor reported by many authors is herd size, where the disease was more prevalent in intensive rearing or feed lots or organised farms or farms with more than 10 animals compared to free-range Bovine Alphaherpesvirus-1 (BoHV-1) Infection in Cattle: An Overview of Epidemiology, Role of Envelope Proteins in Disease and.. animals or the unorganised sector (Rajkhowa et al, 2004).…”
Section: Epidemiologymentioning
confidence: 98%
“…Disease was found to affect exotic and crossbred cattle in India during inception than native breeds. In Slovenia and Colombia HF cow breed (Hostnik et al, 2021) and in Nepal's Jersey breed of cattle have shown higher prevalence than other breeds (Sanjay et al, 2022). One frequent risk factor reported by many authors is herd size, where the disease was more prevalent in intensive rearing or feed lots or organised farms or farms with more than 10 animals compared to free-range Bovine Alphaherpesvirus-1 (BoHV-1) Infection in Cattle: An Overview of Epidemiology, Role of Envelope Proteins in Disease and.. animals or the unorganised sector (Rajkhowa et al, 2004).…”
Section: Epidemiologymentioning
confidence: 98%